A Comprehensive Investigation to Reveal the Relationship Between Plasmacytoid Dendritic Cells and Breast Cancer by Multiomics Data Analysis - Tian, Saisai; Yan, Li; Fu, Lu; Zhang, Zhen; Zhang, Jinbo; Meng, Guofeng; Zhang, Weidong (Frontiers in Cell and Developmental Biology, 2021)
Plasmacytoid dendritic cells (pDC) are an essential component of the immune microenvironment. They have been reported for crucial roles in linking the innate and adaptive immune systems. However, the prognostic role of pDC in breast cancer (BRCA) was controversial. In this work, we collected large sample cohorts and did a comprehensive investigation to reveal the relationship between pDC and BRCA by multiomics data analysis. We found that high pDC abundance was correlated with prolonged survival in BRCA patients. The distinct mutation landscape and lower burden of somatic copy number alterations (SCNA) and lower intratumoral heterogeneity were observed in the high pDC abundance group. Additionally, a more sensitive immune response and chemotherapies response also were observed in high pDC group, which implicates that the patients with high pDC abundance can be benefited from the combination of chemotherapy and immunotherapy. In conclusion, we reported a positive correlation between the pDC abundance and breast cancer patients’ overall survival; we identified the molecular profiles of in the breast cancer patients with pDC abundance; our findings may be beneficial in aiding in the development of immunotherapy and shedding new light on the precision treatment of BRCA.